2018
DOI: 10.1063/1.5037310
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the divacancy and hydrogen in silicon: Observation of fast and slow kinetics

Abstract: The divacancy (V 2) is one of the fundamental defects in silicon. However, the interaction of V 2 with hydrogen is still not fully understood. In the present work, deep level transient spectroscopy (DLTS) results on hydrogen-assisted annealing of V 2 are presented. H þ ions were implanted with multiple energies into n-type Czochralski-grown samples, yielding uniform (box-like) concentration-versus-depth profiles of V 2 and hydrogen in the region probed by the DLTS measurements. The evolution kinetics of V 2 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…In the first approximation, deep levels are caused by point defects of either intrinsic or extrinsic origin; however, extended defects like complexes or even dislocations can exhibit mid-bandgap electronic signatures too. 26,27 In more complex semiconductors, such as β-Ga 2 O 3 , with a number of inequivalent lattice sites, the probability of building complexes may only increase. Generally speaking, judging from our observations, the origin of E3*, E5, and E6 may be due to either (i) generation of new intrinsic point defects, (ii) in-diffusion of the mobile defects from the bulk of the sample, or (iii) changing the configuration of already existing defects.…”
Section: Discussionmentioning
confidence: 99%
“…In the first approximation, deep levels are caused by point defects of either intrinsic or extrinsic origin; however, extended defects like complexes or even dislocations can exhibit mid-bandgap electronic signatures too. 26,27 In more complex semiconductors, such as β-Ga 2 O 3 , with a number of inequivalent lattice sites, the probability of building complexes may only increase. Generally speaking, judging from our observations, the origin of E3*, E5, and E6 may be due to either (i) generation of new intrinsic point defects, (ii) in-diffusion of the mobile defects from the bulk of the sample, or (iii) changing the configuration of already existing defects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Holston et al [16] observed an EPR signal in neutron-irradiated ZnO, which they assigned to the Zn-O divacancy. Moreover, both isolated and hydrogenated divacancies have been identified in H-implanted silicon [17]. However, seeing as there are three off-site configurations of V Ga in β-Ga 2 O 3 [5], in addition to the five simple monovacancies, the resulting V Ga V O can occur in a plethora of different configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported on a hydrogen-related level, labeled as E5 * [8]. The level forms during heat treatments in the temperature range 75 °C-95 °C and has a position at E c − 0.42 eV (E c being the conduction band minimum) and an apparent capture cross-section (CCS) of 4 × 10 −17 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A detailed annealing study of the implantation-induced defects at 75 °C-95 °C observed two processes with different rates [8]. The process with a faster rate is related to the dissociation of phosphorus-hydrogen (P-H) pairs and formation of vacancy-oxygen-hydrogen (VOH) and divacancyhydrogen (V 2 H) complexes by reactions with H i released from P-H.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation